L-carnitine ameliorates bile duct ligation induced liver fibrosis via reducing the nitrosative stress in experimental animals: preclinical evidences - Vikram Nimbalkar (Elsevier, 2021)
Bile duct ligation (BDL) has been extensively used in studying the mechanisms of fibrogenesis and anti-fibrotic drugs. Considering the liver regenerative capacity and the diverse results from BDL, the present study aimed to evaluate the protective effect of L-carnitine on bile duct ligation-induced liver fibrosis in experimental rats. Rats were randomly divided into seven groups (n = 6). The bile duct was ligated and serum aspartate transaminase (AST), alanine transaminase (ALT), total bilirubin and albumin, hepatic hydroxyproline (HP), reduced glutathione (GSH), and malondialdehyde (MDA) and cytokines were measured. iNOS expression was measured by using Western blot and finally, liver tissue was processed for histopathological analysis (H&E staining)”. The level of iNOS was increased in the control group, whereas a decrease in the level of iNOS was found in the L-carnitine treated group. In the present study, we found that bile duct ligation in rats showed an increase in body and liver weight, while treatment with carnitine showed normal body and liver weight. Serum AST, ALT, total bilirubin, HP, GSH, MDA, and cytokines were increased in bile duct ligated rats. In addition, L-carnitine treated rats showed a reduction in oxidative stress as well as inhibiting the release of cytokines in a dose-dependent manner and showed protection against bile duct ligation. The study concludes that L-carnitine has a protective effect against the liver fibrosis induced by bile duct ligation.